German-French Military and Armament Cooperation. Current State and Perspectives (Economic and Political Thought, 2023)
The article attempts to analyze cooperation between Germany and France on the military level. The author tries to present the most important initiatives in the field of both military and armament cooperation of both countries on the bilateral and European level after the end of the Cold War. In particular, attention is paid to the period after the outbreak of a full-scale war in Ukraine. This conflict contributed to adjustments in strategy and defense at the European and national level in both partners. The question still remains whether the war between Russia and Ukraine will become a catalyst for a significant and long-term strengthening and intensification of military and arms cooperation.
Keywords: Germany, France, NATO, European Union, defense, military cooperation, armaments